Specifics of investing in different segments of the financial market of the Russian economy - S. A. Anesyants (Новые технологии)
The article explores one of the most pressing issues facing both individuals and legal entities: «How can you find investment tools that will save your money from inflation and increase it to the extent possible in the conditions of the modern Russian eco-nomy ?» The problem is that of the currently existing financial instruments each has specific features in terms of liquidity, reliability and profitability, and the purpose of the study is to choose the one that reflects adequately the state of the Russian market from the whole range of investment instruments. In the study of the above mentioned problems, the basic methods of research are the elements of fundamental and technical analysis. As a result of the study, factors reflecting the liquidity, reliability and profitability of major investment instruments in modern conditions have been identified, and on the basis of the above analysis, key conclusions have been made about the pros and cons of investing in various financial instruments, taking into account modern Russian socio-economic realities. These conclusions allow us to choose the most appropriate investment instruments, taking into account the strategy and the time period for the formation of the stock portfolio with the help of which we will be able to solve the problem of saving our money from inflation and, if possible, multiplying it.